Vibration control of a cluster of buildings through the Vibrating Barrier. (15th February 2018) - Tombari, A.; Garcia Espinosa, M.; Alexander, N.A.; Cacciola, P.
Highlights: Use of the structure-soil-structure interaction for vibration control of buildings. Verification and validation of the efficiency of the Vibrating Barrier. Over 70% of reduction of the accelerations is achieved for a cluster of buildings. Abstract: A novel device, called Vibrating Barrier (ViBa), that aims to reduce the vibrations of adjacent structures subjected to ground motion waves has been recently proposed. The ViBa is a structure buried in the soil and detached from surrounding buildings that is able to absorb a significant portion of the dynamic energy arising from the ground motion. The working principle exploits the dynamic interaction among vibrating structures due to the propagation of waves through the soil, namely the structure–soil–structure interaction. In this paper the efficiency of the ViBa is investigated to control the vibrations of a cluster of buildings. To this aim, a discrete model of structures-site interaction involving multiple buildings and the ViBa is developed where the effects of the soil on the structures, i.e. the soil-structure interaction (SSI), the structure-soil-structure interaction (SSSI) as well as the ViBa-soil-structures interaction are taken into account by means of linear elastic springs. Closed-form solutions are derived to design the ViBa in the case of harmonic excitation from the analysis of the discrete model. Advanced finite element numerical simulations are performed in order to assess the efficiency of the ViBa for protecting more than a single building. Parametric studies are also conducted to identify beneficial/adverse effects in the use of the proposed vibration control strategy to protect cluster of buildings. Finally, experimental shake table tests are performed to a prototype of a cluster of two buildings protected by the ViBa device for validating the proposed numerical models.